Reactive sputtering of CoZrTaOx thin films - Zheng, Cheng (Nanyang Technological University, 2022)
As a novel metal oxide material with promising electrical properties, CoZrTaOx (OCZT) requires precise control of conditons in the reactive sputtering process to ensure that deposited thin films demonstrate stable and favorable qualities. As the properties of OCZT thin films to process conditions is not well explored, this report aims to study the effects of annealing, Ar/O2 gas flow and target condition on the microstructure and film properties of OCZT thin films. TEM, SAD and XRD are used to characterize the grains of OCZT thin films, while EDX and ToF-SIMS results are analyzed to understand the change in elemental and compound compositions with varying process conditions. Transport of atoms is discussed as the mechanism for crystallization of OCZT thin films. Heat supplied during annealing serves as the driving force for oxygen atoms to overcome kinetic barriers and form metal-oxide compounds. Berg model is reviewed and modified to explain the hysteresis phenomenon in transition sputtering mode. OCZT thin films deposited at transition mode display disparate electrical and mechanical properties. The results of this report suggest that Ar/O2 is a necessary control in the reactive sputtering of metal oxide thin films as it imposes profound impact on deposition rate, film compostions and properties.